2015
DOI: 10.1186/s12864-015-1269-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing and analysis of the entomopathogenic fungus Hirsutella sinensis isolated from Ophiocordyceps sinensis

Abstract: BackgroundOphiocordyceps sinensis, a worm and fungus combined mixture which Hirsutella sinensis is parasitic on the caterpillar body, has been used as a traditional medicine or healthy food in China for thousands of years. H. sinensis is reported as the only correct anamorph of O. sinensis and its main active ingredients are similar to the natural O. sinensis.ResultsH. sinensis L0106, asexual strain of O. sinensis, was isolated and identified in this study. Three transcriptomes of H. sinensis at different cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 67 publications
2
66
0
Order By: Relevance
“…However, the transcriptome analyses using EST library sequencing of stroma of O. sinensis revealed more expressed genes (9,641) (Xiang et al, 2014) than the genome prediction by Hu et al (2013). Even more surprisingly, a total of 12,980 unigenes were found to be expressed in cultured mycelia of the species in a recent study (Liu et al, 2015). The secondary metabolism clusters were largely conserved between O. sinensis and other insect pathogens (Hu et al, 2013) and enzymes associated with carbohydrate metabolism were found to be expressed (Xiang et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the transcriptome analyses using EST library sequencing of stroma of O. sinensis revealed more expressed genes (9,641) (Xiang et al, 2014) than the genome prediction by Hu et al (2013). Even more surprisingly, a total of 12,980 unigenes were found to be expressed in cultured mycelia of the species in a recent study (Liu et al, 2015). The secondary metabolism clusters were largely conserved between O. sinensis and other insect pathogens (Hu et al, 2013) and enzymes associated with carbohydrate metabolism were found to be expressed (Xiang et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…The estimated genome size (120 Mb) is approximately three times larger than other insect ascomycete pathogens due to repeat driven expansion. Their number of predicted genes (6,972) was much fewer than that of a closely related fungus, Cordyceps militaris (9,684), with a much smaller genome size (32.2 Mb) (Zheng et al, 2011), and also fewer than the number of expressed genes detected from transcriptome analysis of O. sinensis (Xiang et al, 2014;Liu et al, 2015). This first draft genome assembly of O. sinensis is likely far from complete.…”
Section: Introductionmentioning
confidence: 95%
“…e analysis rstly maps all DEGs to GO terms in the database (http://www.geneontology. org/), calculating gene numbers for every term, then using ultra-geometric test to nd signi cantly enriched GO terms in DEGs comparing to the genome background [31]. e calculating formula is shown as follows:…”
Section: Gene Ontology and Kegg Pathway Enrichmentmentioning
confidence: 99%
“…These technologies also promote research progress in the eld of traditional Chinese medicine. Since 2010, RNA-seq technology has been used in Chinese herbal medicines (Chen et al 2011;Liu et al 2015;Fukushima et al 2016).…”
Section: Introductionmentioning
confidence: 99%